Hepatitis C Seroconversion Remains High among Patients with Regular Hemodialysis: Study of Associated Risk Factors - Ni Wayan Wina Dharmesti; I Dewa Nyoman Wibawa; Yenny Kandarini (International Journal of Hepatology)
Background/Aims. Hemodialysis patients have a higher risk of hepatitis C compared to the general population. The burden of hepatitis C infection among hemodialysis patients is substantial and was estimated to rise constantly. This study is aimed at determining the frequency of HCV seroconversion and associated risk factors among hemodialysis patients in our unit. Methods. An analytical cross-sectional study involving patients from 2 dialysis units (1 referral hospital and 1 private dialysis unit) in Denpasar, Bali, Indonesia, from January 2020 to December 2021. We evaluated age, gender, duration of hemodialysis, vascular access, history of transfusion, history of surgery, diabetes mellitus, hepatitis B, human immunodeficiency virus (HIV) infection, and type of dialyzer as possible risk factors of hepatitis C seroconversion among hemodialysis patients. Results. A total of 338 hemodialysis patients were enrolled in this study. We found hepatitis C seroconversion in 94 patients (27.8%), all of which occurred after regular dialysis was started. Vascular access type (OR 42.07, 95% CI 5.757–307.472) and dialyzer reuse (OR 8.324, 95% CI 4.319–16.044) were showing a statistically significant association with hepatitis C seroconversion. A separate analysis on each dialysis unit found common evidence that the duration of dialysis was significantly associated with hepatitis C infection among hemodialysis patients. Conclusion. Hepatitis C seroconversion among dialysis patients remains high. Factors related to the dialysis procedure itself played a major role in transmitting the virus.